The Urge to learn English: Breaking the Stigma of English as Bahasa Kafir (Infidel Language) - Zaitun Qamariah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
English is often considered a "Bahasa Kafir" or infidel language and is associated with Western values conflicted with certain religious beliefs. This literature research explores the origins of this stigma and why English is perceived as such. This article aims to break the stigma associated with English by analyzing cultural, historical, and religious contexts. Through a literature review, researchers highlight the importance of understanding that language is a universal communication tool not tied to a particular religion or culture. In contrast, English has values that transcend cultural and religious boundaries. Although such stigma can hinder access to educational and professional opportunities, a deeper understanding of English can broaden our view of the world, open the door to cross-cultural collaboration, and promote a deeper understanding of human diversity. Therefore, examining why English is considered a “Bahasa kafir” can provide valuable insight into how cultural biases and prejudices can influence how people think and interact.